Resuscitate! : how your community can improve survival from sudden cardiac arrest - Eisenberg, Mickey S. (University of Washington Press, 2013)
Sudden cardiac arrest is the leading cause of death among adults, yet it need not be fatal. Though survival in most communities is very poor, a few communities achieve rates as high as 50%. Why are some communities so successful in snatching life from the jaws of death? This book describes the steps any EMS system can take to improve cardiac arrest survival. It is written for the medical directors, administrative directors, fire chiefs, dispatch directors, and program supervisor who direct and run EMS systems all across the country, and for the EMTs, paramedics, and dispatchers who provide frontline care.